Identification of new biosignatures for clinical outcomes in stable coronary artery disease - The study protocol and initial observations of a prospective follow-up study in Taiwan. Issue 1 (December 2017) - Leu, Hsin-Bang; Yin, Wei-Hsian; Tseng, Wei-Kung; Wu, Yen-Wen; Lin, Tsung-Hsien; Yeh, Hung-I; Chang, Kuan-Cheng; Wang, Ji-Hung; Wu, Chau-Chung; Chen, Jaw-Wen
Abstract Background Either classic or novel biomarkers have not been well investigated for clinical outcomes of coronary artery disease (CAD) in Asian people especially ethnic Chinese. We reported here a prospective national-based follow-up study that aims to elucidate the clinical profiles and to identify the new biosignatures (especially the non-lipid profile and inflammatory biomakers) for future clinical outcomes in a sizable cohort of stable CAD patients in Taiwan. Methods A total of 2500 CAD patients under stable condition after successful percutaneous coronary intervention will be enrolled for clinical data collection and blood/urine sampling in northern, southern, western, or eastern part of Taiwan between 2012 and 2017. They will be regularly followed up at least annually for 5 years to assess all cause deaths, hard clinical events (including cardiovascular death, nonfatal myocardial infarction, nonfatal stroke), and total cardiovascular events (including hard events, unplanned revascularization procedures, unplanned hospitalization for refractory or unstable angina, and for other causes such as stroke, transient ischemic attack, heart failure, or peripheral arterial occlusive disease). The classic and newly defined biosignatures will be compared in patients with and without clinical events during follow-up. The novel biomarkers will be identified via metabolomics analyses. Additionally, psychological personality and lifestyle data will be incorporated to explore the new dimensional views of the complex mechanisms of the disease. Till December 2014, the initial 1663 patients have been successfully enrolled. Among them, 85.93% are male; 36.22% have type 2 diabetes; 64.82% have hypertension; 56.04% are smokers and 20.44% have a family history of CAD. Their lipid profiles are under contemporary medical control with a mean plasma total cholesterol level of 163.51 ± 36.99 mg/dL and a mean low-density lipoprotein cholesterol level of 95.21 ± 29.98 mg/dL. Discussion This nationwide study has successfully started to update the contemporary information and to investigate the potential predictors for clinical outcomes of stable CAD patients in Taiwan. The identification of new biomarkers, lifestyle and psychological personality may help to elucidate the complex mechanisms and provide the novel rational to the individual treatment strategies in Asian especially ethnic Chinese patients with CAD.